Intersectionality, health equity, and EDI: What's the difference for health researchers? - Christine Kelly; Lisette Dansereau; Jennifer Sebring; Katie Aubrecht; Maggie FitzGerald; Yeonjung Lee; Allison Williams; Barbara Hamilton-Hinch (BMC, 2022)
Abstract Many countries adopted comprehensive national initiatives to promote equity in higher education with the goal of transforming the culture of research. Major health research funders are supporting this work through calls for projects that focus on equity, resulting in a proliferation of theoretical frameworks including "intersectionality," "health equity," and variations of equity, diversity and inclusion, or EDI. This commentary is geared at individual principal investigators and health research teams who are developing research proposals and want to consider equity issues in their research, perhaps for the first time. We present histories and definitions of three commonly used frameworks: intersectionality, health equity, and EDI. In the context of health research, intersectionality is a methodology (a combination of epistemology and techniques) that can identify the relationships among individual identities and systems of oppression; however, it should also be used internally by research teams to reflect on the production of knowledge. Health equity is a societal goal that operationalizes the social determinants of health to document and address health disparities at the population level. EDI initiatives measure and track progress within organizations or teams and are best suited to inform the infrastructure and human resourcing "behind the scenes" of a project. We encourage researchers to consider these definitions and strive to tangibly move health research towards equity both in the topics we study and in the ways we do research.